Antecedents of word-of-mouth communication and purchase intention on Facebook - Bogdan Anastasiei; Ana Raluca Chiosa (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2018)
More and more business customers use social media to express their opinions about products, services and brands. This study aims to make a step further in understanding consumer engagement in electronic word of mouth (eWOM) on Facebook and its impact on recommending and purchasing products. To test our conceptual framework, structural equation modeling techniques have been applied to data collected through a self-administrated survey addressed to 640 Facebook users from Romania. Our model shows that Facebook's perceived usefulness infl uences customer brand engagement, which in turn has an important effect on the intention to purchase the brand and recommend it to others (word of mouth). Therefore, people who use Facebook as a source of information about products and services are top eWOM providers. A brand that seeks to build authority on Facebook should look for eWOM providers, convert them into fans and "feed" them with attention-grabbing information that is worth spreading. This way, most of the fans will provide free word-of-mouth advertising, becoming true brand ambassadors. Our study has established that Facebook's perceived usefulness not only engages online users with brands, but also makes this medium a perfect eWOM tool: it builds trust in friends' recommendations, and eventually, makes the users sincere supporters of the brands they like.
Keywords: M31; M37; 650; electronic word of mouth; brand engagement; referral intention; recommendations; purchase intention; social media